Chromosome-level genome assembly of Patagonian moray cod (Muraenolepis orangiensis) and immune deficiency of major histocompatibility complex (MHC) class II - Kim, Jinmu; Lee, Seung Jae; Jo, Euna; Choi, Eunkyung; Cho, Minjoo; Choi, Soyun; Kim, Jeong-Hoon; Park, Hyun (Frontiers in Marine Science, 2023)
The Patagonian moray cod, Muraenolepis orangiensis, belongs to the family Muraenolepididae and is the sole order of Gadiformes that inhabits the temperate and cold waters of the southern hemisphere. In this study, a high-quality chromosome-level genome assembly was constructed, resulting in a final assembled genome of 893.75 Mb, with an N50 scaffold length of 30.07 Mb and the longest scaffold being 39.77 Mb. Twenty-five high-quality pseudochromosomes were assembled, and the complete BUSCO rate was 93.4%. A total of 34,553 genes were structurally annotated, and 27,691 genes were functionally annotated. One of the features of the Gadiformes order is that they have a remarkably unique immune gene repertoire that influences innate and adaptive immunity, and they lack major histocompatibility complex (MHC) class II, invariant chains (CD74), and CD4 genes. Among the 10 primary genes involved in MHC class II, only two ERAP1 genes and one AIRE gene were identified through the genome study. Although no specific reason for the MHC class II deficiency has been identified, it has been shown that the toll-like receptors (TLRs), which are significant to the innate immune response, are significantly expanded in M. orangiensis. A total of 44 TLRs have been identified, with 32 TLR13 genes distributed evenly on six different pseudochromosomes. This study is the first to reveal the whole genome of a Muraenolepididae family and provides valuable insights into the potential rationale for the MHC class II deficiency in a Gadiformes fish species.